2005
DOI: 10.1021/jp052817q
|View full text |Cite
|
Sign up to set email alerts
|

Molecules with Large-Amplitude Torsional Motion Partially Oriented in a Nematic Liquid Crystal:  Ethane and Isotopomers

Abstract: An NMR study on ethane and five isotopomers dissolved in the nematic liquid crystal Merck ZLI 1132 is performed. A consistent set of dipolar and quadrupolar couplings is obtained. The dipolar couplings are corrected for harmonic vibrational effects, while the contribution from the torsional motion is incorporated classically. The corrected dipolar couplings cannot be understood in terms of a reasonable molecular structure unless effects of the reorientation-vibration interaction are taken into account. Assumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 44 publications
1
27
0
Order By: Relevance
“…Finally, a new term was found which involved a coupling between non-totally symmetric solute normal modes and reorientational motion. This contribution (the vibration-reorientation interaction) is present for all solutes, and forms a serious impediment in obtaining highly accurate structures from observed dipolar couplings [21][22][23]. In the literature [24] one is often confronted with the notion that solutes could be distorted by the liquid-crystal environment, and that such a distortion could explain the observed dipolar couplings in the methanes.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a new term was found which involved a coupling between non-totally symmetric solute normal modes and reorientational motion. This contribution (the vibration-reorientation interaction) is present for all solutes, and forms a serious impediment in obtaining highly accurate structures from observed dipolar couplings [21][22][23]. In the literature [24] one is often confronted with the notion that solutes could be distorted by the liquid-crystal environment, and that such a distortion could explain the observed dipolar couplings in the methanes.…”
Section: Introductionmentioning
confidence: 99%
“…The seven highly accurate independent dipolar couplings obtained from each spectrum are used to obtain four fitting parameters for each of two models, namely two model prefactors for orientational ordering (w n for CCd and k and k s for CI (2k)) with the remaining two being the E ext tg and the CCH angle increase which accounts for vibrational-reorientational effects [28][29][30][31]. These fitting parameters are shown in Tables 2 and 3 for the CCd and CI (2k) orientational models.…”
mentioning
confidence: 99%
“…However, detailed studies of methyl groups in methyl fluoride, methyl iodide, and ethane have shown that vibration-reorientation interaction effects are transferable among methyl groups in different molecules, and when neglected lead to an apparent increase in the methyl HCH angle. [34][35][36] Large rms values are obtained unless a similar distortion is included in the pentane analysis. Except for this crude inclusion of vibration-reorientation effects, other small-amplitude vibrational effects are neglected.…”
Section: Resultsmentioning
confidence: 99%